2016
DOI: 10.1007/s00586-016-4624-z
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic analysis of cervical spine canal diameter and its association with grade of degeneration

Abstract: C5/6 and C4/5 is of higher risk of suffering SCI than other levels, C4/5 level predispose SCI at earlier stage than C5/6, patients presenting with intermediate signal and slight decreased disc height on T2 weighted MRI at C4/5 level should be paid attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
2
1
0
Order By: Relevance
“…Moreover, in our research, we found that the IVDs at C6-C7 showed higher mean ADC value than the IVDs at C5-C6, at which the lowest mean ADC value was reached. The same finding was reported by Teraguchi et al [ 20 ] in a large-scale epidemiology survey about cervical disc degeneration, in which they found the prevalence of disc degeneration was highest at C5-C6, followed by C6-C7 and C4-C5, due to its largest range of motion among all cervical discs [ 21 ].…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, in our research, we found that the IVDs at C6-C7 showed higher mean ADC value than the IVDs at C5-C6, at which the lowest mean ADC value was reached. The same finding was reported by Teraguchi et al [ 20 ] in a large-scale epidemiology survey about cervical disc degeneration, in which they found the prevalence of disc degeneration was highest at C5-C6, followed by C6-C7 and C4-C5, due to its largest range of motion among all cervical discs [ 21 ].…”
Section: Discussionsupporting
confidence: 81%
“…C4/5 had the lowest spinal canal diameter and C5/6 had the second-lowest spinal canal diameter, both in the neutral and extension positions. C4/5 (3/13) and C5/6 (5/13) had higher risks of injury than the other levels, which has been corroborated by a previous kinematic analysis [ 28 ]. Ito et al [ 27 ] used a biofidelic model to simulate whiplash and found that spinal cord injury during whiplash is unlikely to occur in patients with normal average canal diameters.…”
Section: Discussionsupporting
confidence: 78%
“…C4/5 had the lowest spinal canal diameter and C5/6 had the second-lowest spinal canal diameter, both in the neutral and extension positions. C4/5 (3/13) and C5/6 (5/13) had higher risks of injury than the other levels, which has been corroborated by a previous kinematic analysis [33]. Ito et al [32] used a bio delic model to simulate whiplash and found that spinal cord injury during whiplash is unlikely to occur in patients with normal average canal diameters.…”
Section: Discussionmentioning
confidence: 65%